Between image and identity : transnational fantasy, symbolic violence, and feminist misrecognition - Eileraas, Karina, 1971- (Lexington Books, 2007)
This book addresses the 'autobiographical' literature, visual, and performance art of postcolonial women from Maghreb and Southeast Asia including Leila Sebbar, Assia Djebar, and Theresa Hak Kyung Cha. Karina Eileraas critically examines how contemporary postcolonial artists participate in the violence of representation in order to re-imagine the relationship between image and identity.